1983
DOI: 10.1111/j.1365-3180.1983.tb00545.x
|View full text |Cite
|
Sign up to set email alerts
|

The persistence and metabolism of isoproturon in soil

Abstract: Summary The persistence of isoproturon in soil in pot experiments was the same whether or not the soil contained growing wheat (Triticum aestivum L.) plants, Panllel) work with radioactive isoproturon showed that the breakdown products were the same in the presence and absence of plants. Persistence in the field was reasonably well predicted by a simulation model using the results of laboratory incubation studies and field meteorological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 9 publications
4
35
0
Order By: Relevance
“…In soil from two sites along transect 2 (sites B and C), degradation showed first-order kinetics, with no rapid phase of degradation, and approximately 15% IPU remained after 65 days. In all sites, HPLC analysis revealed the temporary appearance of peaks with identical retention times to 3-(4-isopropyl-phenyl)-1-methylurea (MDIPU) and 3-(4-isopropyl-phenyl)-urea (data not shown), indicating that metabolism of IPU occurred by sequential N-demethylation, as outlined by Mudd et al (16).…”
Section: Resultssupporting
confidence: 52%
“…In soil from two sites along transect 2 (sites B and C), degradation showed first-order kinetics, with no rapid phase of degradation, and approximately 15% IPU remained after 65 days. In all sites, HPLC analysis revealed the temporary appearance of peaks with identical retention times to 3-(4-isopropyl-phenyl)-1-methylurea (MDIPU) and 3-(4-isopropyl-phenyl)-urea (data not shown), indicating that metabolism of IPU occurred by sequential N-demethylation, as outlined by Mudd et al (16).…”
Section: Resultssupporting
confidence: 52%
“…6, step 1). MDIPU has previously been reported to be the main metabolite produced during the degradation of IPU in agricultural soils (4,6,13,16,19,22). An alternative metabolic pathway involving initial hydroxylation of the isopropyl side chain resulting in 2-hydroxy-IPU [3-(4-(2-hydroxyisopropyl)-phenyl)-1,1-dimethylurea] has also been described in agricultural soils (19,32).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of its widespread and repeated use, IPU is frequently detected in groundwater and surface waters in Europe in levels exceeding the European Commission drinking water limit of 0.1 g l Ϫ1 (23,33,34). Degradation of IPU in agricultural soils occurs predominantly by microbiological processes (6,22). Several studies have demonstrated a slow natural attenuation rate in various soils and subsurface environments with respect to mineralization of the phenyl structure (4,15,17,18,26,35).…”
mentioning
confidence: 99%
“…The detection limit is 0.01 ppm. The period of study was suitable for dissipation of pesticide from crops to reach less than maximum residue limit permitted by Food Agriculture Organization (FAO) and World Health Organization(WHO) [16] .…”
Section: Resultsmentioning
confidence: 99%